2019
DOI: 10.2139/ssrn.3372973
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Resolution of DLX-Orchestrated Transcriptional Circuits Driving Development of Forebrain GABAergic Neurons

Abstract: Lindtner et al. reveal the regulatory wiring organized by DLX transcription factors in forebrain GABAergic neuronal specification, by integrating functional genomic, epigenomic, and genetic data on a transgenic mouse model. This network determines key sequence-encoded regulatory elements and implicates a combination of histone modifications and biophysical interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 65 publications
1
37
0
Order By: Relevance
“…Our analyses indicate that the ventral Gsx2 à Ascl1 à Dlx1/2 transcriptional pathway is enriched in ShhPCs. This is consistent with some ShhPCs being committed to the OB-IN lineage (Zhang et al, 2020), as this pathway is important for generating OB-INs (Guo et al, 2019;Lindtner et al, 2019). In addition to its roles in neurogenesis, Ascl1 genetically interacts with Olig2 and is critical for normal production of oligodendrocytes in the spinal cord and ventral forebrain (Nakatani et al, 2013;Parras et al, 2007;Sugimori et al, 2007).…”
Section: Cross-repressive Gene Regulatory Network For Neurogenesis Asupporting
confidence: 69%
See 1 more Smart Citation
“…Our analyses indicate that the ventral Gsx2 à Ascl1 à Dlx1/2 transcriptional pathway is enriched in ShhPCs. This is consistent with some ShhPCs being committed to the OB-IN lineage (Zhang et al, 2020), as this pathway is important for generating OB-INs (Guo et al, 2019;Lindtner et al, 2019). In addition to its roles in neurogenesis, Ascl1 genetically interacts with Olig2 and is critical for normal production of oligodendrocytes in the spinal cord and ventral forebrain (Nakatani et al, 2013;Parras et al, 2007;Sugimori et al, 2007).…”
Section: Cross-repressive Gene Regulatory Network For Neurogenesis Asupporting
confidence: 69%
“…In the developing chick forebrain, Dlx1/2 are necessary and sufficient to repress oligodendrocyte specification via transcriptional inhibition of Olig2 (Jiang et al, 2020). Dlx1/2 also repress Gsx2 (Guo et al, 2019) and activate Sp8 and Sp9 expression (Lindtner et al, 2019), which are essential for OB-IN maturation (Guo et al, 2019;Li et al, 2018). Pax6 is also required to generate a subset of OB-INs (Kohwi et al, 2005), and we found that Pax6 levels are initially decreased in ShhPCs before increasing again specifically in the OB-IN lineage.…”
Section: Cross-repressive Gene Regulatory Network For Neurogenesis Amentioning
confidence: 54%
“…It has been proposed that interactions between Prdm family proteins and bHLH transcription factors is a conserved mechanism for the regulation of gene expression during neural development (Hohenauer and Moore, 2012;Ross et al, 2012). Such transcription factor complexes may function in the proliferative zones where they are expressed in order to direct differentiation/lineage progression programs towards region-specific neuronal subtype specification (Lindtner et al, 2019). Our genomic analysis of PRDM16 binding in MGE progenitors sheds light on the lineage-specific transcriptional programs regulated by PRDM16 and suggests that specialized PRDM16-associated protein complexes may orchestrate these programs in different progenitor types.…”
Section: Discussionmentioning
confidence: 99%
“…Like Ascl1, the Dlx genes require Gsx2 for their correct expression in LGE progenitors (Toresson et al, 2000, Corbin et al, 2000, Yun et al, 2001, Wang et al, 2013). Both Ascl1 and Dlx factors have been shown to promote the differentiation of GABAergic neuronal phenotypes typical of the LGE (Yun et al, 2002, Long et al, 2009a, 2009b, Pla et al, 2018, Lindtner et al, 2019). Furthermore, loss of Gsx2 leads to an upregulation of the oligodendrocyte precursor cell marker Pdgfr α (Corbin et al, 2003) and concomitant precocious oligodendrocyte differentiation (Chapman et al, 2013, 2018).…”
Section: Discussionmentioning
confidence: 99%